The performance of block decoding using Dorsch algorithm / Husna Abdul Rahman, Ros Shilawani S. Abdul Kadir and Farah Yasmin Abdul Rahman. - Abdul Rahman, Husna; S. Abdul Kadir, Ros Shilawani; Abdul Rahman, Farah Yasmin (2007)
The aim of this project is to investigate the Dorsch algorithm performance in the decoding process of various block codes. The error performance of both the decoding method are evaluated, compared and concluded. The conventional decoding method is hard decision based whereby the message of the demodulator is quantized only to two levels. The demodulator makes a firm decision whether a bit is a 0 or a 1, which are called hard bits. The demodulator does not tell the decoder how reliable this decision is. An important feature of the Dorsch algorithm is that it uses soft decision decoding. Soft decision occurs if the output of the demodulator, which are the soft bits is quantized to more than two levels. These soft bits are the measure of confidence for each decision. The decoding based on soft bits are referred to as soft decision decoding. The algorithm uses soft decision information to rank the reliability of the received symbols. The high reliability symbols are treated as the soft decision of the information values whereas the low reliability symbols are treated as parity checks for the information values. The high reliability symbols are called the information set and the low reliability symbols are called the parity set.